Statistics of chromatin organization during cell differentiation revealed by heterogeneous cross-linked polymers - O. Shukron (Nature Portfolio, 2019)
Chromatin is folded into Topologically Associating domains (TADs), with the organization and folding hierarchy of the TADs being highly dynamic. Here the authors develop a parsimonious randomly cross-linked (RCL) polymer model that maps high frequency encounters present in Hi-C data within and between TADs and reconstruct TADs across cell differentiation, revealing local chromatin re-organization.